Reinventing Samosir Tourism: An Innovative Model of Community-Based Regenerative Tourism for Ecological Justice and Prosperity - Daryana, Aditiya Pratama; Yudhistira, Prima (Journal of Rural and Regional Innovation Studies, 2025)
This study aims to explore and analyze the application of a regenerative community-based tourism model in Samosir Regency, focusing on socio-economic impacts, cultural preservation, and environmental sustainability. The methods used include in-depth interviews, participatory observations, Focus Group Discussions (FGDs), and document studies, involving local communities, tourism managers, and tourists. The results show that the tourism sector makes a significant contribution to the local economy, with about 30% of household income coming from tourism, despite inequality in the distribution of benefits. In addition, there has been a positive increase in environmental awareness, but challenges remain related to waste management in remote areas. Community involvement in tourism management is high, although there is still a dependence on external stakeholders. From a cultural perspective, this model supports the preservation of local culture, although there is a risk of cultural commodification that needs to be watched out. In conclusion, while regenerative tourism provides great benefits, challenges related to income distribution, equitable environmental management, and cultural commodification must be addressed to achieve long-term sustainability. Further research is needed to develop a more equitable model of profit distribution and strengthen the capacity of local communities in more autonomous tourism management.